Aplikasi Geolistrik pada Pemetaan Daerah Intrusi Air Laut di Pantai Candidasa - Pujianiki, Ni Nyoman; Simpen, I Nengah (Department of Civil Engineering, Diponegoro University, 2018)
To know the magnitude of sea water intrusion that occurred in Candidasa area need to be mapping by using Geo-electric Method. Geo-electric method is one Geophysical method that works by injecting an electric current into the ground and then measured the potential difference it generates. Based on the data of electric current and potential difference, resistivity will be obtained in the research area. The result of sea water intrusion mapping in Candi Dasa beach area indicates that sea water intrusion has occurred but not yet on the status of conspiracy. If groundwater extraction is not restricted, the level of intrusion will continue to increase. Contour resistivity indicates that there has been a sea water intrusion in the Candidasa Tourism Area in a mild status in the southeast area at a depth of 5-10 m. The measured rock resistivity values in the study sites ranged from 0.35 to 1800 ohm.m, the seawater intrusion criteria occurred at a resistivity of 0.5 - 30 ohm.m. The results of the study are expected to give policyholders input on sea water intrusion in Candidasa Tourism area so that appropriate policy steps can be taken.